Two books of Ezekiel : Papyrus 967 and the Masoretic text as variant literary editions - Lilly, Ingrid E. (Leiden ; Boston : Brill, 2012)
Employing text-critical, literary, and codicological analysis, this books shows the significance of papyrus 967 for understanding the book of Ezekiel's textual transmission and status as a variant literary edition.
Print version record.
Includes bibliographical references and indexes.
Master record variable field(s) change: 630
Keywords: Bible. -- Criticism, Textual; Papyrus 967.; Bible. -- Versions -- Papyrus 967.; Bible. -- Criticism, interpretation, etc; Bible; Bible. -- Versions -- Papyrus 967.; Bible; Religion; RELIGION -- Biblical Studies -- Prophets; Electronic books